Productos digitales sobre la " GUERRA DE BANDAS" de Cuicuno, parroquia Guaytacama, cantón Latacunga. - Chancusig Toaquiza, Doris Maribel (2020)
The purpose of this research project stems from the need to publicize the popular music of Cuicuno, through a digital product that shows the musical history, exhibited in the Contest Bands. With the participation of the “ La gran K-Leña” Band against to the “Señor del Arbol” band, the hand-in-hand of 2019 was performed, showing their talent and excitement on stage. Event that attracts devotees, local and national tourists; the event is done in the festivities in homage of the patron “Señor del Arbol”, image of the Crucified Christ carved in a “quishuar” tree. From this, the question arises: How will graphic design contribute to the dissemination of the historical musical wealth of the Contest Band and the hand-in-hand of 2019 between the “Señor del Arbol” band and the “K-Leña” band in the Cuicuno neighborhood, Guaytacama Parish of the Latacunga city. To solve the question it was considered to make a digital product that shows the musical history of the “K-Leña”and “Señor del Arbol” band, and the participation in the Contest Band. The methodology applied for data collection and characteristic of the problem began with the mapping to the Cuicuno neighborhood, obtaining the location of the musical groups, who provided the promotional material for the analysis of the graphic styles used for its dissemination. Through the interview and observation techniques addressed to the directors, musicians and president of the party committee, the history and evolution of the participating bands for the elaboration of the digital product was obtained as information. Similarly, we chose to work with the Bruce Acher methodology, with the aim of satisfying the need to spread the musical richness of the leading groups in the Contest Bands. The development of a digital product that tells the story based on the idea, plot, narrative, literary and technical script was determined. Taking into account the analytical, creative and executive phase mentioned by the author, the development and functionality of a storytelling was determined. This product will contribute to the dissemination of the participating musical groups’ hand-in-hand of 2019. Supporting the revaluation of the music that Cuicuno neighborhood owns with the sixteen bands represented by the “K-Leña” and “Señor del Arbol” bands, in the Contest Bands.